Manajemen Kegawatdaruratan Bersihan Jalan Nafas Tidak Efektif dengan Hisap Lendir pada Pasien Stroke di RSUD Pandan Arang Boyolali - Yuniati; Tri Susilo (Universitas Ngudi Waluyo, 2025)
Stroke is a medical emergency that can lead to respiratory problems due to the accumulation of secretions, particularly in patients with decreased consciousness. One of the common nursing problems encountered is ineffective airway clearance. This study aims to describe the emergency management of ineffective airway clearance through mucus suction in stroke patients at the Emergency Department of Pandan Arang Hospital, Boyolali. This research used a descriptive case study approach. The subject was a stroke patient with decreased consciousness and signs of secretion accumulation in the airway. Data collection methods included observation, interviews, physical examination, and supporting investigations. Nursing interventions included airway assessment, semi-Fowler positioning, insertion of an oropharyngeal airway (OPA), suctioning for less than 15 seconds, oxygen administration at 3 L/min via nasal cannula, and collaboration in administering mucolytics. The intervention was implemented over a one-hour duration. The results showed a decrease in gurgling sounds, reduced sputum production, and improved breathing patterns. The nursing diagnosis of “ineffective airway clearance” was resolved. This study suggests that early detection and appropriate management of ineffective airway clearance through suction are essential to prevent further respiratory complications in stroke patients. Nurses are encouraged to enhance their skills and responsiveness in managing airway emergencies. ABSTRAK Stroke merupakan kegawatdaruratan medis yang dapat menyebabkan gangguan pernapasan akibat akumulasi sekret, terutama pada pasien dengan penurunan kesadaran. Salah satu masalah keperawatan yang sering muncul adalah bersihan jalan napas tidak efektif. Tujuan penelitian ini adalah untuk menggambarkan manajemen kegawatdaruratan bersihan jalan napas tidak efektif melalui tindakan hisap lendir pada pasien stroke di IGD RSUD Pandan Arang Boyolali. Penelitian ini menggunakan pendekatan deskriptif dengan metode studi kasus. Subjek penelitian adalah seorang pasien stroke dengan gangguan kesadaran dan tanda-tanda akumulasi sekret di jalan napas. Data dikumpulkan melalui observasi, wawancara, pengkajian fisik, dan pemeriksaan penunjang. Intervensi keperawatan yang dilakukan meliputi: pengkajian jalan napas, pemberian posisi semi-Fowler, pemasangan oropharyngeal airway (OPA) , tindakan hisap lendir kurang dari 15 detik, pemberian oksigen 5 L/menit melalui nasal kanul, dan kolaborasi pemberian mukolitik. Implementasi dilakukan dalam durasi 1 jam. Hasil yang diperoleh menunjukkan adanya penurunan suara gurgling, sputum menjadi berkurang, dan pola napas membaik. Masalah keperawatan